Quinazolin-4-one derivatives lacking toxicity-producing attributes as glucokinase activators: design, synthesis, molecular docking, and in-silico ADMET prediction - Saurabh C. Khadse; Nikhil D. Amnerkar; Manasi U. Dave; Deepak K. Lokwani; Ravindra R. Patil; Vinod G. Ugale; Nitin B. Charbe; Vivekanand A. Chatpalliwar (SpringerOpen, 2019)
Abstract Background A small library of quinazolin-4-one clubbed thiazole acetates/acetamides lacking toxicity-producing functionalities was designed, synthesized, and evaluated for antidiabetic potential as glucokinase activators (GKA). Molecular docking studies were done in the allosteric site of the human glucokinase (PDB ID: 1V4S) enzyme to assess the binding mode and interactions of synthesized hits for best-fit conformations. All the compounds were evaluated by in vitro enzymatic assay for GK activation. Results Data showed that compounds 3 (EC50 = 632 nM) and 4 (EC50 = 516 nM) showed maximum GK activation compared to the standards RO-281675 and piragliatin. Based on the results of the in vitro enzyme assay, docking studies, and substitution pattern, selected compounds were tested for their glucose-lowering effect in vivo by oral glucose tolerance test (OGTT) in normal rats. Compounds 3 (133 mg/dL) and 4 (135 mg/dL) exhibited prominent activity by lowering the glucose level to almost normal, eliciting the results in parallel to enzyme assay and docking studies. Binding free energy, hydrogen bonding, and π-π interactions of most active quinazolin-4-one derivatives 3 and 4 with key amino acid residues of the 1V4S enzyme were studied precisely. Preliminary in-silico absorption, distribution, metabolism, excretion, and toxicity (ADMET) prediction was carried out using SwissADME and PreADMET online software which revealed that all the compounds have the potential to become orally active antidiabetic agents as they obeyed Lipinski's rule of five. Conclusion The results revealed that the designed lead could be significant for the strategic design of safe, effective, and orally bioavailable quinazolinone derivatives as glucokinase activators.